Erratum: JEAN CLAUDE RAKOTONIRINA & BRIAN L. FISHER (2013) Revision of the Pachycondyla wasmannii- group (Hymenoptera: Formicidae) from the Malagasy region. Zootaxa, 3609 (2), 101–141. - Rakotonirina, Jean Claude; Fisher, Brian L. (Zootaxa, 2013)
(Erratum)